Le modèle de la reproduction sociale à l’épreuve des migrations - Marie Verhoeven (Recherches Sociologiques et Anthropologiques)
This article questions the relevance of Bourdieu’s Reproduction model for understanding the specific nature of educational inequalities experienced by children from immigrant backgrounds. Contrary to the common thesis that inequalities linked to migratory or ethnocultural origin are “dissolvable” into social inequalities, the article revisits a body of quantitative and qualitative research conducted in French-speaking Belgium, supporting the hypothesis of a specific vulnerability affecting this population. A close examination of statistical analyses based on PISA data first reveals several systemic effects (pathway and compositional effects), which point to the mechanisms through which initial capital is processed within school structures and converted into educational hierarchies. The second part draws on international literature to show how the (transnational) migratory experience involves dynamics of requalification and capital creation, which may or may not be recognized and converted within the educational field. The third part mobilizes Bilge’s (2010) “integrated intersectional approach” to move beyond a simple combination of factors (class, ethnicity, gender) and instead grasp how these variables interlock and embed themselves within meso- and micro-level educational structures (local school markets and school micropolitics). The analytical proposals developed in the article aim to remain faithful to the relational and systemic dimensions of the Reproduction model, while expanding it to include global migratory and local intersectional dynamics.